Chlorzoxazone, an SK channel activator used in humans, reduces excessive alcohol intake in rats - Hopf, F. Woodward (2010)
BACKGROUND: Alcoholism imposes a tremendous social and economic burden. There are relatively few pharmacological treatments for alcoholism, with only moderate efficacy, and there is considerable interest in identifying additional therapeutic options. Alcohol exposure alters SK-type potassium channel (SK) function in limbic brain regions. Thus, positive SK modulators such as chlorzoxazone (CZX), an FDA-approved centrally-acting myorelaxant, might enhance SK function and decrease neuronal activity, resulting in reduced alcohol intake. METHODS: We examined whether CZX reduced alcohol consumption under two-bottle choice (20% alcohol and water) in rats with intermittent access to alcohol (IAA) or continuous access to alcohol (CAA). In addition, we used ex vivo electrophysiology to determine whether SK inhibition and activation can alter firing of nucleus accumbens (NAcb) core medium spiny neurons. RESULTS: CZX significantly and dose-dependently decreased alcohol but not water intake in IAA rats, with no effects in CAA rats. CZX also reduced alcohol preference in IAA but not CAA rats, and reduced the tendency for rapid initial alcohol consumption in IAA rats. CZX reduction of IAA drinking was not explained by locomotor effects. Finally, NAcb core neurons ex vivo showed enhanced firing, reduced SK regulation of firing, and greater CZX inhibition of firing in IAA versus CAA rats. CONCLUSIONS: The potent CZX-induced reduction of excessive IAA alcohol intake, with no effect on the more moderate intake in CAA rats, may reflect the greater CZX reduction in IAA NAcb core firing observed ex vivo. Thus, CZX could represent a novel and immediately accessible pharmacotherapeutic intervention for human alcoholism.